Addiction in the time of COVID-19: Longitudinal course of substance use, psychological distress, and loneliness among a transnational Tyrolean sample with substance use disorders - Lommer, Kilian; Schurr, Timo; Frajo-Apor, Beatrice; Plattner, Barbara; Chernova, Anna; Conca, Andreas; Fronthaler, Martin; Haring, Christian; Holzner, Bernhard; Macina, Christian; Marksteiner, Josef; Miller, Carl; et al. (Frontiers in Psychiatry, 2022)
Introduction: Next to an increased use of alcohol, the current pandemic has been associated with increased psychological distress among the general population. Research on its effects on individuals suffering from substance use disorders (SUD) is scarce. This study aimed at expanding the existing literature on this topic with a focus on the impact of loneliness and perceived social support. Methods: Sixty-eight people diagnosed with SUD according to ICD-10 from the Austrian state of Tyrol and from the Italian Province of South Tyrol who had been treated in a psychiatric hospital in 2019 and one hundred and thirty-six matched reference subjects of the same regional background participated in an online survey. Sociodemographic variables and scores on the Brief Symptom Checklist, the Three-Item Loneliness Scale, and the Multidimensional Scale of Perceived Social Support were collected at baseline and five months thereafter. Baseline took place after the first wave, while follow-up largely coincided with the second wave of the pandemic. Results: Among both patients and the matched reference group, substance use as a means to feel better facing the pandemic rose and predicted higher levels of psychological distress. Patients were less likely to receive specific care at follow-up than at baseline and presented with a significantly higher prevalence of clinically relevant psychological distress and loneliness than the matched reference group at both assessment times. Among both groups, psychological burden remained unchanged over time. Perceived social support was generally significantly higher in the matched reference group than in patients. Loneliness and, to a lesser degree, low perceived social support predicted psychological distress. Conclusion: These findings emphasize the need of preventive and educational measures regarding substance use behavior for both individuals suffering from SUD and those without mental health disorders.